analisis blibiometrik terhadap berpikir kreatif matematika siswa: berpikir kreatif matematika - Nur Azira (Jurnal Pustaka Cendekia Pendidikan, 2024)
In studying mathematics, everyone must be able to think well in order to cultivate high-level reasoning abilities which are the targets of learning mathematics. Reflective thinking ability is one of the classifications of higher order thinking skills that must be mastered properly. Through this research the aim is to be able to know the classification of mathematical reflective thinking skills with bibliometric analysis. This study utilizes Harzing's Publish or Perish (POP) software with Google Scholar sources with the keywords "Mathematically Reflective Thinking" and "Mathematics Education" which have been filtered according to theme and analyzed using VOSviewer software. There are many terms in research on the ability to think reflectively, but the terms evidence and implementation are rarely used in research..